Eco-Friendly Water Purification: Harnessing Natural Coagulants for Sustainable Treatment - Agnes Preethi Lourduraj,; U Gowtham Kishore,; K Veerendra,; P Sai Srinivas, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Access to clean and safe drinking water remains a critical global challenge, necessitating effective and sustainable water treatment methods. This Project conducted a comparative investigation to assess the efficacy of natural coagulants—neem powder and orange peel powder—in treating wastewater samples. Samples were collected from a single source and treated using both conventional chemical methods and natural coagulants, followed by natural sedimentation. Key parameters, including pH, total dissolved solids (TDS), total suspended solids (TSS), and turbidity, were measured to evaluate treatment effectiveness. While chemical treatment initially showed superior results, its drawbacks made it less desirable. In contrast, natural coagulants produced promising outcomes within acceptable limits, highlighting their potential as a sustainable and eco-friendly alternative. The Project emphasizes the need for further research to optimize natural coagulants for safe and accessible drinking water.
Keywords: Water treatment; Natural coagulants; Neem powder; Orange peel powder; Wastewater; Sustainability; Eco-friendly